Determinants of foreign aid in family planning: How relevant is the Mexico City Policy? - Elizabeth Asiedu; Malokele Nanivazo; Mwanza Nkusu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The Mexico City Policy (MCP) prohibits the United States Agency for International Development from providing aid to international non-governmental organizations that provide abortion-related services. This paper employs a panel data of 151 developing countries over the period of 1988 - 2010, to examine the effect of the MCP on the allocation of family planning aid to developing countries. We find that the MCP has a negative and robust effect on family planning aid. We also find that family planning aid to countries in sub-Saharan Africa (SSA) is higher than aid to non-SSA countries, and that high fertility rate countries as well as highly populated countries tend to receive more family planning aid.
Keywords: F23; D72; 330; family planning; foreign aid; Mexico City Policy; sub-Saharan Africa